2021
DOI: 10.1016/j.ijid.2021.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotype Distribution of Human Papillomavirus Infection among 12 076 Iranian Women

Abstract: Introduction: Human papillomavirus (HPV) infection is one of the major health concerns of women in developing countries. This study gives an insight into the prevalence and genotype distribution of HPV infection and compares it with Pap smear results among Iranian women.Methods: In this study, 12 076 Iranian women underwent routine examination from November 2016 to November 2018 using HPV Direct Flow CHIP System for HPV DNA typing. Cytology was undertaken for 5138 samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
6
17
0
Order By: Relevance
“…In agreement with previous studies [ [37] , [38] , [39] ], among the HR genotypes, HPV genotype 16 was the most common genotype detected in our study, whereas the most common LR genotype was HPV genotype 6. Our results agree with previous studies conducted in Turkey where HPV type 16 and type 18 prevalence was reported to be the most common HPV genotypes [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies [ [37] , [38] , [39] ], among the HR genotypes, HPV genotype 16 was the most common genotype detected in our study, whereas the most common LR genotype was HPV genotype 6. Our results agree with previous studies conducted in Turkey where HPV type 16 and type 18 prevalence was reported to be the most common HPV genotypes [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Present study showed that both genders showed a somehow high HPV prevalence; 55.7% and 52% for men and women, respectively. Other national published observations indicated the prevalence of HPV infection in cervical/vaginal secretions between 5.5% and 57.4% of females with different study populations and methodologies [ 11 , 21 , 23 27 ]. Nevertheless, HPV in Iranian males in four studies ranged between 9.5 and 54% [ 19 21 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sabet et al found that in both genders, 26–35 years old contained more than half of HPV positive cases [ 28 ]. Bitarafan et al found that 26–46 years old group contained the most frequent HPV positivity [ 27 ]. One of the key messages raised form those above Iranian investigations could be the necessity for prompt targeted immunization against HPV for ages between 20 and 40 or even earlier age periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems HPV infection is not restricted to a specific age group although the rate of HPV infections is more distinguished in subjects with unsafe sexual activities and multiple partners. 8,10,25,[30][31][32][33][34][35][36][37][38][39][40][41][42] In the current cross-sectional descriptive study, the highest prevalence rate of HPV genotypes (56.64%) was observed in the 25-34 years age group of 1, 133 cervical scrapping specimens. Our finding revealed that HPV genotypes detected were remarkable in the general population and multiple HPV genotypes were also observed as asymptomatic forms.…”
mentioning
confidence: 99%